Development of a replication‐deficient adenoviral vector‐based vaccine candidate for the interception of HPV16‐ and HPV18‐induced infections and disease. Issue 2 (24th April 2017) - Khan, Selina; Oosterhuis, Koen; Wunderlich, Kerstin; Bunnik, Evelien M.; Bhaggoe, Melissa; Boedhoe, Satish; Karia, Santusha; Steenbergen, Renske D.M.; Bosch, Leontien; Serroyen, Jan; Janssen, Sarah; Schuitemaker, Hanneke; et al.
Abstract : High‐risk Human papilloma virus (HPV) types are the causative agents of cervical cancer and several other anogenital malignancies. The viral proteins expressed in the (pre)malignant cells are considered ideal targets for immunological intervention. Many approaches have been evaluated for this purpose, mostly aiming at the induction of HPV16 E7‐ and/or E6‐specific cellular immunogenicity. As clinical success has so far been limited, novel approaches are required. We describe the development and pre‐clinical testing of a vaccine candidate consisting of replication‐deficient adenovirus type 26 and 35 based vectors for the interception of HPV16‐ and HPV18‐related disease. We developed HPV16‐ and HPV18‐specific antigens consisting of fusion proteins of E2, E6 and E7. The vaccine will be suitable for every disease stage, from incident and persistent infections where E2 is predominantly expressed up to late stages where E6 and E7 expression are upregulated. Importantly E6 and E7 are present as reordered fragments to abrogate the transforming activity of these two proteins. Loss of transforming activity was demonstrated in different in vitro models. Robust T‐cell immunogenicity was induced upon immunization of mice with the vaccine candidate. Finally, the developed vaccine vectors showed considerable therapeutic efficacy in the TC‐1 mouse model. The absence of transforming activity of the antigens and the favorable immunogenicity profile of the adenovirus based vectors along with the fact that these vectors can be readily produced on a large scale makes this approach attractive for clinical evaluation. Abstract : What's new? The authors highlight the design, development and preclinical testing of a therapeutic vaccine against highly cancerogenic human papilloma virus (HPV) type 16 and 18 (HPV16/HPV18). The vaccine is based on replication‐deficient recombinant Adenoviral vectors serotypes 26/35, which can be manufactured under Good Manufacturing Practices (GMP), are highly immunogenic and show therapeutic efficacy in a mouse model.